Dampak Bulying Pada Psikologi Anak Usia Dini Dan Progam Pencegahan Pemerintah - Nuri Arifiah Romadhoni (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
Bullying is a form of abuse or violence, which is carried out directly by one person or a stronger group. Bullying is bullying that is carried out physically against others and is carried out continuously, bullying is bullying that is carried out repeatedly by stronger actors against weaker actors, carried out deliberately and carried out to complete their tasks physically and emotionally.